Modeling as a Decision Support Tool for Bovine TB Control Programs in Wildlife - Smith, Graham C.; Delahay, Richard J. (Frontiers in Veterinary Science, 2018)
Computer modelling has a long history of association with epidemiology, including wildlife diseases. This work has led to much greater understanding of the theory of disease dynamics and how to empirically manage wildlife diseases. A summary of the badger bovine TB models and their involvement with decision making is presented. Early work looked at R0, the ratio of new infections per infected individual that arrives in a naive population. Values close to unity imply that the disease should be easy to control. Various estimations for bovine TB in cattle and badgers, and in possums, have put the R0 at not much higher than unity. However, disease control in badgers appears to be more challenging than anticipated. For control by vaccination, most models implicitly assume full protection of the individual from infection, although the available vaccine (BCG) is only partial protective. Descriptions of how models could better represent the ecological and epidemiological complexities of the badger-cattle TB system are presented, along with a wider discussion of the utility of modelling for bovine TB management interventions. This includes consideration of the information required to maximise the utility of the next generation of models.